Romania - Poverty Monitoring Analytical and Advisory Assistance Program : Are the Most Vulnerable Protected? - World Bank (Washington, DC, 2012)
The rapid economic growth since 2000 has been the main driver of poverty reduction in Romania. However, even under the current positive growth scenario, there are still people who live in poverty, and some who are unlikely to benefit from future growth and thus may continue to be left behind. For these people an effective redistributive social policy and targeted interventions are needed. The purpose of this note is to assist the Ministry of Labor, Family and Equal Opportunities (MLFEO) to analyze and monitor the effectiveness of the main social safety net benefits to fight social exclusion and reduce poverty. To determine the extent to which social transfers offer protection to the poorest groups of the population, the paper uses the last available (2004-2006) rounds of the household budget survey data. The analysis presented here uses the consumption aggregate and the absolute poverty definition presented in the 2003 and 2007 poverty assessments. Three main indicators are used to assess the effectiveness of social protection (SP) programs: coverage (share of population covered by the programs), targeting (share of funds directed to each welfare group of population), and adequacy of benefit (share of the benefit in the consumption of beneficiaries). The paper begins with a review of the main findings, followed by an overview of the social protection system and its overall effectiveness. Then it assesses the main social assistance programs, and concludes with a review of key issues.